Stability and chemical demulsification of water-in-crude oil emulsion (chemical method) - Tam, Siow Fui (2010)
The formation of water-in-crude oil(W/O)emulsion can be encountered at many stages during drilling,producing, transporting and processing of crude oils. A good understanding of petroleum emulsions is necessary for the intention to control and enhance the processes in all these stages.In this study,both chemical and physicochemical properties of W/O emulsions that prepared by using cocamide DEA(non-ionic and biodegradable surfactant that synthesized from coconut oil) and three types of conventional chemical emulsifiers(span 83, SDDS, triton X-100)were investigated. 50-50% W/O emulsions were prepared at 800rpm (mixing speed) with three different concentrations of each emulsifier. These emulsions were tested for relative rates of water separation(stability test),viscosity,shear stress,and shear rate at varied temperature and stirring speed of Brookfield viscometer.Results shown that span 83 and cocamide DEA were both effective.For chemical demulsification,demulsifiers with different concentrations were used to treat 50-50 and 20-80% W/O emulsions prepared at varied mixing speed.The relative rates of water separation were characterized via beaker tests.Coco amine and palm-based oleyl amine (synthesized from coconut oil and palm oil)were concluded to promote the best coalescence of droplets in compared with others conventional demulsifiers: hexylamine,PEG 600,and propylene glycol.